The Persistence of Long-Run Abnormal Returns: Evidence from Stock Repurchases and Offerings - FU, Fangjian (Institutional Knowledge at Singapore Management University, 2012)
Prior studies have documented that stock returns are abnormally high during the years following share repurchases and abnormally low following seasoned equity offerings, relative to various benchmarks of expected returns. While we confirm this evidence in the event data as of 2002, we do not find robust long-run abnormal returns following either stock repurchases or issuances after 2002. Institutional ownership of event stocks has increased substantially in the recent decade, which helps to explain the disappearance of the abnormal performance following corporate stock transactions. The evidence seems consistent with the improved stock market efficiency in recent years, accompanied by reduced trading costs, popularization of algorithmic trading, and increased institutional investment activity, as documented by a number of recent studies. Also consistent with the improved market efficiency, fewer firms in the recent years conduct stock repurchases or seasoned equity offerings for the purpose of timing the market.